2005
DOI: 10.1038/labinvest.3700233
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of major histocompatibility complex antigens in invading glioma cells: stealth invasion of the brain

Abstract: Invasion into surrounding brain tissue is a fundamental feature of gliomas and the major reason for treatment failure. The process of brain invasion in gliomas is not well understood. Differences in gene expression and/or gene products between invading and noninvading glioma cells may identify potential targets for new therapies. To look for genes associated with glioma invasion, we first employed Affymetrix microarray Genechip s technology to identify genes differentially expressed in migrating glioma cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 60 publications
5
108
0
8
Order By: Relevance
“…It was previously reported that renal cell carcinomas and other tumors downregulate expression of the MHC I and II HLA genes (Gastl et al, 1996;Osborne et al, 1997;Atkins et al, 2004;Satoh et al, 2004;Zagzag et al, 2005). As it is commonly believed that abnormalities in antigen presentation may help tumors evade the full-scale immune response (Seliger et al, 2000), the molecular mechanisms of such deficiencies may provide a clue to novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that renal cell carcinomas and other tumors downregulate expression of the MHC I and II HLA genes (Gastl et al, 1996;Osborne et al, 1997;Atkins et al, 2004;Satoh et al, 2004;Zagzag et al, 2005). As it is commonly believed that abnormalities in antigen presentation may help tumors evade the full-scale immune response (Seliger et al, 2000), the molecular mechanisms of such deficiencies may provide a clue to novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Further study of their functions and expressions in glioma tissue or cell lines will improve our knowledge of their roles as potential circulating biomarkers for high-grade glioma. A2M has been found to be synthesized and secreted by human glioma cells and up-regulated in migrating human glioma cells compared with non-migrating glioma cells (21). The A2M receptor, LRP, is overexpressed in human malignant astrocytomas, especially in GBM (22), and A2M can cross the blood-brain barrier in an LRP-dependent manner (23).…”
Section: Discussionmentioning
confidence: 99%
“…A Perier et al to downregulate HLA-I and II genes (Osborne et al, 1997;Atkins et al, 2004;Zagzag et al, 2005). Abnormalities in the expression of HLA molecules altering antigen presentation may contribute to tumors evading the adaptive immune response (Seliger et al, 2000), but promote NK activation.…”
Section: Mutated Vhl Rcc Cells and Nk Cell Activationmentioning
confidence: 99%